Analisis Manajemen Risiko Kredit Pada Produk Kredit Pemilikan Rumah BTN - Yunia Safitri; Abel Tasman (Universitas Negeri Padang, 2021)
The aims of this study is to find out : (1) what the character of problematic debtorts of PT. Bank Tabungan Negara (Persero), Tbk Padang Branch Office, (2) what the factors that cause bad credit of PT. Bank Tabungan Negara (Persero), Tbk Padang Branch Office, (3) how credit rsik management of housing loans at PT. Bank Tabungan Negara (Persero), Tbk Padang Branch Office. This type of research is a qualitative descriptive study. This study using by purposive sampling, while the source and some information through in-depth interviews or in-depth interviews and direct observations to the object of the researcher. Secondary data that supports this research are obtained from documents available at the research site. To test the validity of the data used source triangulation. The results showed that the debtor's character could be seen from the 5C analysis. The factors that cause non-performing loans are internal and external factors. Even though there is a problematic debtor character that causes bad credit on KPR, in this case BTN Padang Branch Office has been good at minimizing this, there is a good flow of risk management analysis. In order to identify risks and implement the checklist, you will be able to review the risks of applying qualitative and quantitative methods. This measurement is not only carried out for customers but also for developers who want to work with BTN. Keywords : Risk management, non-performing loans, mortgage loans